2000
DOI: 10.1016/s0893-133x(99)00100-1
|View full text |Cite
|
Sign up to set email alerts
|

Strain Differences in the Behavioral Effects of Antidepressant Drugs in the Rat Forced Swimming Test

Abstract: -Kyoto (WKY) rats provide a model of stressinduced depressive behavior, because they show enhanced vulnerability to the effects of stressors. The present study examined differences in the behavioral response to different types of antidepressant drugs between WKY and SpragueDawley (SD) rats in the forced swimming test (FST). WKY rats displayed significantly greater immobility than SD rats during their exposure to the FST. The noradrenergic antidepressant, desipramine, produced a dose-dependent reduction of immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
156
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(176 citation statements)
references
References 35 publications
16
156
4
Order By: Relevance
“…The nature of this variability, whether there are intrinsic differences in susceptibility to stress or differences in baseline locomotor activity, remains to be elucidated [1]. Our studies were in agreement with previous studies that have shown similar differences in mobility between inbred strains [14,19,35].…”
Section: Discussionsupporting
confidence: 91%
“…The nature of this variability, whether there are intrinsic differences in susceptibility to stress or differences in baseline locomotor activity, remains to be elucidated [1]. Our studies were in agreement with previous studies that have shown similar differences in mobility between inbred strains [14,19,35].…”
Section: Discussionsupporting
confidence: 91%
“…18,[23][24][25][26][27]31,33 Their behavior in the FST and several other behavioral tests provide strong evidence that WKY rats are in a depressive-like state. While both WKY and F344 females exhibit high levels of immobility, WKY females did exhibit decreased climbing in the FST relative to F344 females.…”
Section: Discussionmentioning
confidence: 97%
“…5 The Wistar Kyoto (WKY) rat exhibits depressivelike behavior in a number of behavioral tests. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Among the behavioral tests that indicate a depressivelike state in the WKY, we chose to work with the forced swim test (FST), a measure frequently used to test for antidepressant drugs. This test is used in animal models to test for 'behavioral despair' [35][36][37][38] and/or 'passive coping behavior'.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the WKY have been proposed as an animal model of depressive behavior because they consistently demonstrate exaggerated behavioral and physiologic responses to stress in a variety of situations when compared with other strains (Pare 1993(Pare , 1994. Indeed, the WKY strain demonstrates higher levels of behavioral immobility at baseline in the forced swimming test (a rodent test sensitive to antidepressant drugs) and in open field (Pare 1994;Lopez-Rubalcava and Lucki 2000). Thus, these rats possess a combination of behavioral and neurochemical (dopamine-related) characteristics that make them interesting models in their own right.…”
Section: Discussionmentioning
confidence: 99%